The Influence of Motivation and Work Goals on Employee Performance in Organizations - Syafitri, Elsa Bernafia; Astuti, Dwi (Review: Journal of Multidisciplinary in Social Sciences, 2025)
The purpose of this study is to find out how much work goals and employee motivation influence their performance in the organization. It is hoped that the results of this research will provide practical and majority advantages. In general, the results of this research are expected to improve the repertoire of social sciences, especially in the field of human resources. Overall, it is hoped that the results of this study can make a positive contribution to businesses in terms of improving their performance. This research was conducted using a quantitative method with 70 respondents. The results of data processing showed that employees had high motivation scores for their performance. An R square (R2) value of 53.2% indicates this, with an additional 46.2% influenced by other components not discussed in this study. Research shows that PT Panasonic Gobel Energy Indonesia increases work motivation. Therefore, research should be conducted further on the same subject but by considering additional variables such as individual abilities, work environment, and other factors that are directly involved.